2011
DOI: 10.1111/j.1445-6664.2011.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanism of Leptochloa chinensis Nees to propanil

Abstract: The resistance mechanism of Leptochloa chinensis Nees to propanil was investigated, based on propanil metabolism, aryl acylamidase activity, and chlorophyll fluorescence at the 8 week growth stage of L. chinensis.The concentration of propanil in the leaf and culm extracts of the resistant (R) and susceptible (S) biotypes, as measured by gas chromatography (GC), was found to increase after propanil treatment.The concentration of propanil in the leaf and culm extracts of the S biotype at 72 h was 1.55 and 0.49 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…At 72 HAT, there were greater 3,4‐DCA concentrations in Cd‐PS tissue in the absence of carbaryl relative to Cd‐PR tissue that had received carbaryl. Cd‐PS tissue had higher 3,4‐DCA concentrations than Cd‐PR among treatments at 72 HAT, a major difference from previous studies in which propanil‐R weeds accumulated 3,4‐DCA concentrations several‐fold greater than S biotypes owing to metabolic resistance . Nonetheless, 3,4‐DCA levels in Cd‐PR might have been reduced by growth and expansion of propanil‐free tissue, which contributes to the dilution of both propanil and 3,4‐DCA in plant tissue, since the entire above‐ground tissue was harvested for this study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At 72 HAT, there were greater 3,4‐DCA concentrations in Cd‐PS tissue in the absence of carbaryl relative to Cd‐PR tissue that had received carbaryl. Cd‐PS tissue had higher 3,4‐DCA concentrations than Cd‐PR among treatments at 72 HAT, a major difference from previous studies in which propanil‐R weeds accumulated 3,4‐DCA concentrations several‐fold greater than S biotypes owing to metabolic resistance . Nonetheless, 3,4‐DCA levels in Cd‐PR might have been reduced by growth and expansion of propanil‐free tissue, which contributes to the dilution of both propanil and 3,4‐DCA in plant tissue, since the entire above‐ground tissue was harvested for this study.…”
Section: Resultssupporting
confidence: 93%
“…GR 50 and LD 50 showed a 14‐ and 18‐fold increase in Cd‐PR resistance levels relative to Cd‐PS (Figs A and B respectively). The level of propanil resistance in C. difformis is substantially higher than the levels reported for propanil‐R Echinochloa colona , E. crus‐galli and Leptochloa chinensis . Levels of propanil resistance in these grasses ranged between 1.5‐fold and eightfold.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This resistance level is greater than levels reported for propanil-R grass weeds, such as barnyardgrass [Echinochloa crus-galli (L.) Beauv. ], junglerice [Echinochloa colona (L.) Link], and Chinese sprangletop [Leptochloa chinensis (L.) Nees] (Fischer et al 1993;Juliano et al 2010;Sahid et al 2011), which had 1.5-to 8-fold increased levels of resistance. Resistance in the aforementioned weeds was later attributed to enhanced propanil metabolism, suggesting propanil resistance in ricefield bulrush might be conferred by another mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the dose-response assays that were conducted by Juliano et al (2010), it is likely that the resistance mechanism of the biotypes that were observed in the Philippines also was related to the enhanced metabolism of the propanil herbicide, including when used in combination with butachlor. Similarly, Sahid et al (2011) reported that enhanced metabolism due to increased arylacylamidase activity is also the resistance mechanism in propanil-resistant Leptochloa chinensis, which appeared in Malaysia in 2011.…”
Section: Mechanism Of Resistance Of Echinochloa Crus-gallimentioning
confidence: 95%